Additive selection strategy for high performance perovskite photovoltaics - Han, Guifang (2020)
Although much of the initial progress in perovskite solar cells has been made by the archetypal CH3NH3PbI3, incorporation of an additional cation such as formamidinium, cesium, and mixed halides have shown promising results in both stability and device performance. However, the role of the additional cations as well as the mixed halides is yet to be fully understood. In this work, we investigate the role of different additives including group I alkali metal cations (K, Rb, Cs and NH4) and halide anions (Br and I) on double-cation perovskites, i.e., [(MAPbBr3)0.15(FAPbI3)0.85]. A notably longer charge carrier lifetime is achieved for perovskite films with additives and may be attributed to defect passivation. Selection rules are put forward based on the effect of the ionic size of an additive on phase stabilization and defect passivation. Addition of complementary size cation with respect to cation size of the parent perovskite, mainly helps stabilizing the perovskite phase by tuning tolerance factor, while addition of the similar size cation/anion, acts as defect passivator. The performance improvement of devices fabricated using NH4I as additive well supports this hypothesis, and offers yet another pathway toward harnessing the multitude of perovskite compositions to achieve high performing solar cells and perhaps other optoelectronic devices.